A learning factory: Enhancing societal needs awareness and innovation through manufacturing class - Hamouda, A.M.S.; Tarlochan, F. (Engineering Education Letters)
The manufacturing course is a common course in most Mechanical and Industrial Engineering programs around the world. In this course, various aspects of product design and manufacturing process selection are discussed. Students are occasionally given the opportunity to utilize and fabricate some parts by using the discussed manufacturing technologies. To bring further appreciation to the course, the Manufacturing Course in Qatar University has added innovation and entrepreneurship with active learning. Instead of teaching the course material in one daunting block, the faculty (mentor) used a “Just in Time Teaching” strategy by integrating engineering theory and product design within a business plan. The students were divided into groups, and each group had to address a societal need within Qatar. The students were given sessions about idea generation tools and creativity techniques. Once the problem had been identified and formulated, these groups were advised and coached to prepare a comprehensive business plan that included selection of materials, manufacturing processes, organizational structure, marketing of the product, market segmentation and penetration, break-even analysis and economic analysis, as well as environmental issues. From the course assessment and student course outcomes surveys, it was found that the interest and learning curve for students increased drastically for this manufacturing course compared to previous approaches. Besides improving the interest and learning curve, the approach had indirectly exposed the student to project management skills, economic analysis, lifelong learning, communication and teamwork. On the whole, the approach was an interesting and led to further enhancing the student's learning process by using different learning styles through varied and innovative teaching techniques.